Ludisme et allusion dans l’étymologie poétique latine - Cécile Margelidon (Methodos)
The Latin etymological wordplay, although the object of more and more studies, has received few definitional attempts that take into account both the singularity of the ancient etymology and the playful modalities implemented by the poets. Whereas sound echoes and paronyms are the basis of certain ancient etymological connections, it is important to have a poetic approach to the process based on the allusive capacity of the origin of words, and to insist on the playful part of the process.In what way is the origin of words one of the means available to Latin poets to play with the literary, philological and antiquarian knowledge of their readers? How can it enter into a process of connivance with the reader? What are the characteristic features of etymological ludism in its poetic singularities? Of Latin etymological ludism in particular, in its relationships with Greek?